Rheological and Printability Assessments on Biomaterial Inks of Nanocellulose/Photo-Crosslinkable Biopolymer in Light-Aided 3D Printing - Wang, Qingbo; Backman, Oskar; Nuopponen, Markus; Xu, Chunlin; Wang, Xiaoju (Frontiers in Chemical Engineering, 2021)
Biomaterials inks based on cellulose nanofibers (CNFs) and photo cross-linkable biopolymers have great potential as a high-performance ink system in light-aided, hydrogel extrusion-based 3D bioprinting. However, the colloidal stability of surface charged nanofibrils is susceptible to mono-cations in physiological buffers, which complexes the application scenarios of these systems in formulating cell-laden bioinks. In this study, biomaterial inks formulated by neutral and negatively surface charged CNFs (GrowInk-N and GrowInk-T) and photo cross-linkable biopolymers (gelatin methacryloyl (GelMA) and methacrylated galactoglucomannan (GGMMA)) were prepared with Milli-Q water or PBS buffer. Quantitative rheological measurements were performed on the ink formulations to characterise their shear-flow-recovery behaviours and to understand the intermolecular interactions between the CNFs of different kinds with GGMMA or GelMA. Meanwhile, printability assessments, including filament extrudability and shape fidelity of the printed scaffold under varying printing conditions, were carried out to optimise the printing process. Our study provides extensive supporting information for further developing these nanocellulose-based systems into photo-cross-linkable bioinks in service of cell-laden 3D bioprinting.